IMPROVEMENT OF THE MECHANISM FOR IMPLEMENTING SECURITIES TRANSACTIONS BY COMMERCIAL BANKS - Avezov Ibrohim (European Science Publishing, 2026)
This article examines the theoretical aspects of securities transactions of commercial banks, mechanisms for their improvement. The article also studies the organizational, legal and operational mechanisms for conducting securities transactions in banks, examines the problems that hinder their development, and formulates conclusions on the further development of the activities of commercial banks in the securities market.
Keywords: Commercial banks, securities, securities of commercial banks, stock market, diversification, bond, eurobond.